STRATEGI PENGEMBANGAN UMKM SENTRA INDUSTRI TAS KENDAL (SINTAK) MENGGUNAKAN MATRIKS PERUMUSAN STRATEGI - Dian Marlina Verawati; Shinta Ratnawati; Hanung Eka Atmaja (Forum Manajemen STIMI Handayani Denpasar, 2018)
The purpose of research is to design the best strategy in developing SMEsKendal Bag Industry Center by looking at the internal and external aspects andconsidering the factors of development of SMEs Kendal Bag Industrial Center soit is necessary to design the strategy appropriately, considering the development ofKendal Bags Industry Center is not good because there are still many shortcomings.The object of this research is in Kendal Bag Industry Center, which is the center ofhandicraftsman in Kendal District, which is trained by Truko villagers in small andmedium enterprises (SMEs). Using the Matrix of Strategy Formulation method. Theresults of the strategy formulation matrix produce a strategy by increasing workingcapital to increase capacity, modify the equipment, and provide credit facilities oncredit to consumers.